2018
DOI: 10.1186/s11556-018-0201-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 10-week walking and walking with home-based resistance training on muscle quality, muscle size, and physical functional tests in healthy older individuals

Abstract: BackgroundOlder individuals have been shown to present muscle atrophy in conjunction with increased fat fraction in some muscles. The proportion of fat and connective tissue within the skeletal muscle can be estimated from axial B-mode ultrasound images using echo intensity (EI). EI was used to calculate the index of muscle quality. Walking, home-based weight-bearing resistance training, and its combinations are considered simple, easy, and practical exercise interventions for older adults. The purpose of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 48 publications
(88 reference statements)
2
40
0
Order By: Relevance
“…Other studies that implemented a similar exercise program also reported improvements in functional capacity and fitness [ 42 , 47 , 71 , 72 , 73 ]. These studies implemented their programs from 8 to 18 weeks, with a frequency of three times per week and a session duration ranging from 50 min to 60 min.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Other studies that implemented a similar exercise program also reported improvements in functional capacity and fitness [ 42 , 47 , 71 , 72 , 73 ]. These studies implemented their programs from 8 to 18 weeks, with a frequency of three times per week and a session duration ranging from 50 min to 60 min.…”
Section: Discussionmentioning
confidence: 84%
“…Therefore, strategies are needed to encourage changes in body composition and physical condition [ 36 , 37 ]. Exercise programs, such as gerontogymnastics, which include resistance and aerobic training, are an optimal strategy for maintaining muscle mass and its protective effects against a variety of chronic diseases [ 38 , 39 , 40 , 41 , 42 ]. However, older adults with low functional capacity may not be able to develop resistance programs leading to improved CRF, due to their low fitness [ 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…This has contributed to a systematic increase in the amount of research concerning health-related effects of various physical training interventions in middle-aged and older people. [18][19][20][21] Physical activity can prevent and reduce the occurrence of musculoskeletal disorders in populations of all ages. [22][23][24][25] However, this is especially important in professionally active workers, as musculoskeletal pain can be the factor that reduces the ability and capacity to work.…”
Section: Introductionmentioning
confidence: 99%
“…The reason for this is that muscle atrophy due to aging is part of several functional disorders, including decreased muscle strength and flexibility, vulnerability to injury, and delayed functional recovery [3][4][5]. Compared to young and middleaged adults, people aged 70-85 years old experience a 30% decrease in muscle mass [6].Resistance training has become a strategy to prevent muscle atrophy [7].It also improves physical function, muscle strength, and the ability to maintain muscle mass [8]. Recently, mechanism-based (power training, eccentric training, high intensity interval training, hybrid electrical stimulation training) interventions incorporated with age-related changes have been attempted in exercise interventions for older adults [9-12].…”
mentioning
confidence: 99%